Pemberdayaan Masyarakat Melalui Pengolahan Serundeng Ikan Nila di Desa Mesjid Punteuet Kota Lhokseumawe - Alfian, Alfian; Nazaruddin, M.; Salma, Salamah (Aceh Journal of Community Engagement (AJCE), 2023)
Meshid Punteuet which is located in Blang Mangat District, Lhokseumawe City, is an area that has extensive fishing grounds such as ponds, most of the people's livelihood is fish farming. Generally, people cultivate tilapia, because tilapia grows quickly and has a high survival rate. The complaint of tilapia farmers is that the selling price of tilapia tends to be low and people's purchasing power is also low. Therefore, it is necessary to process tilapia into diversified products so that it can increase selling power and buyer interest, for this reason it is necessary to empower housewives in the village to utilize cultivated tilapia so that it becomes food, namely serundeng tilapia. This empowerment activity in the form of lecturers' service to the community will be carried out in October 2023. The stages of the service activity consist of preparing tools and materials, surveying the level of understanding and expertise, demonstration of serundeng tilapia processing, training on serundeng tilapia processing, and surveying the level of acceptance of serundeng tilapia fish products. So that it can increase the added value of tilapia fish and can increase selling power and improve community welfare